Endodontic retreatment of apical periodontitis complicated with tooth perforation (Эндодонтия Today, 2020)
Perforation teeth are considered the second most important cause of failure of endodontic treatment. The article puts forward a method of repeated endodontic treatment with «Osteoplast» material application for retreatment of chronic destructive forms of periodontitis, complicated with tooth perforation. We have treated 25 people with chronic destructive periodontal disease at the age of 25-35 years of age with a history of endodontic intervention. The efficiency of application of the proposed comprehensive treatment.